The System of Blood Coagulation in Normal and in Liver Transplantation (Review) - V. I. Reshetnyak; S. V. Zhuravel; N. K. Kuznetsova; V. М. Pisarev; E. V. Klychnikova; V. Е. Syutkin; Т. M. Reshetnyak (Общая реаниматология)
The review dwells on the problem of hemostatic disorders in patients undergoing liver transplantation and their correction in the perioperative period. The physiology of the hemostatic system, disorders of the blood coagulation system in patients at various stages of liver transplantation, correction of hemostatic disorders during and after orthotopic liver transplantation are discussed. Liver transplantation is performed in patients with liver diseases in the terminal stage of liver failure. At the same time, changes in the hemostatic system of these patients pose a significant risk of developing bleeding and/or thrombosis during and after liver transplantation. The hypothesis is suggested that the personalized correction of hemostasis disorder in liver transplantation should be based on considerating the nosological forms of the liver damage, mechanisms of development of recipient’s hemostatic disorders, and the stage of the surgery.